2013
DOI: 10.1093/rheumatology/ket167
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic antiphospholipid syndrome and pregnancy: an experience of 13 cases

Abstract: The occurrence of HELLP syndrome in a patient with APS should raise the suspicion of CAPS in the following days, and anticoagulation should be maintained post-partum or post-abortum. Subsequent pregnancies are at very high risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 24 publications
2
49
0
3
Order By: Relevance
“…A systemic inflammatory syndrome characterized by fever, tachycardia, tachypnea, and leukocytosis commonly coexists and is associated with the extensive ischemic tissue damage [105,106]. Triggering factors identified in most patients include infections, surgery, obstetric complications, drugs or discontinuation of anticoagulants, and others [107,108]. The clinical manifestations are related to the specifics of organ involvement and include severe hypertension, acute renal failure, proteinuria, and hematuria (kidneys); ARDS, pulmonary embolism, and DAH (lungs); hypertensive and/or ischemic encephalopathy and stroke (central nervous system); coronary artery thrombosis and valve lesions (heart), and livedo reticularis, acrocyanosis, purpura, and others (skin) [109,110].…”
Section: Pulmonary Thromboembolism and Capsmentioning
confidence: 99%
“…A systemic inflammatory syndrome characterized by fever, tachycardia, tachypnea, and leukocytosis commonly coexists and is associated with the extensive ischemic tissue damage [105,106]. Triggering factors identified in most patients include infections, surgery, obstetric complications, drugs or discontinuation of anticoagulants, and others [107,108]. The clinical manifestations are related to the specifics of organ involvement and include severe hypertension, acute renal failure, proteinuria, and hematuria (kidneys); ARDS, pulmonary embolism, and DAH (lungs); hypertensive and/or ischemic encephalopathy and stroke (central nervous system); coronary artery thrombosis and valve lesions (heart), and livedo reticularis, acrocyanosis, purpura, and others (skin) [109,110].…”
Section: Pulmonary Thromboembolism and Capsmentioning
confidence: 99%
“…81 Catastrophic thrombotic syndromes during pregnancy Catastrophic APS has been described in patients who were pregnant or in the peripartum period, including patients with known APS during transition from warfarin to LMWH initiated because of pregnancy. 82,83 Patients without APS or other disorders can also develop a severe thrombotic syndrome during pregnancy or in the early postpartum setting. 2,84 Presentation may overlap with other pregnancy-related syndromes, including HELLP (hemolysis, elevated liver enzymes, low platelet count), preeclampsia, and eclampsia.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…2,84 Presentation may overlap with other pregnancy-related syndromes, including HELLP (hemolysis, elevated liver enzymes, low platelet count), preeclampsia, and eclampsia. 83 Anticoagulant therapy is essential, using LMWH early in the pregnancy, and unfractionated heparin around the time of delivery. Steroids, plasma exchange, and/or IV immunoglobulins can be used in pregnant patients presenting with catastrophic APS.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…24 In a small retrospective series of 13 patients with pregnancy-related CAPS, CAPS usually followed HELLP syndrome (n = 12). 25 Therefore, clinicians should be very cautious about this potentially life-threatening condition especially when dealing with HELLP syndrome as CAPS can be lethal in about 50% of the cases. obstetrical complications Recurrent fetal loss and stillbirth A retrospective cohort study conducted from 1988 to 2006 on 1719 patients with unexplained recurrent miscarriages showed that there was no clear correlation between the number of preceding miscarriages and the age of the mother with APS diagnosis.…”
Section: Insights Of Some New Clinical Criteria Of Obstetricalmentioning
confidence: 99%
“…special considerations: preventing catastrophic antiphospholipid syndrome The best admitted treatment for CAPS is based on its prevention, therefore, postpartum period should be covered with 6 weeks of anticoagulation. 25 Once CAPS has been diagnosed, despite the lack of good studies on the treatment and the management of this entity, combined aggressive therapies, for example, with anticoagulants, corticosteroids, plasmapheresis, and rituximab are usually admitted as beneficial. Despite this, CAPS is still lethal in 50% of the cases.…”
Section: Management Of Obstetrical Antiphospholipid Syndromementioning
confidence: 99%